Business Risk Assessment Using Client Strategy Analysis Approach in order to Increase the Efficiency and Effectiveness of the Audit Process - El-Khaldi, Nahed; Nashwan, Iskandar; Kullab, Amani (Journal of Economics and Administrative Sciences, 2018)
Abstract This study aimed to identify the business risks using the approach of the client strategy analysis in order to improve the efficiency and effectiveness of the audit process. A study of business risks and their impact on the efficiency and effectiveness of the audit process has been performed to establish a cognitive framework of the main objective of this study, in which the descriptive analytical method has been adopted. A survey questionnaire has been developed and distributed to the targeted group of audit firms which have profession license from the Auditors Association in the Gaza Strip (63 offices). A hundred questionnaires have been distributed to the study sample of which, a total of 84 where answered and collected. The data were analyzed using (SPSS). The most findings: Auditors are more able to detect internal and external strategic risks for the client, Thus fore, increasing the efficiency and effectiveness of the audit process.